Investigation Of Biology Teacher Candidates' With Ability To Associate Status Of Scientific Information - Gamze Mercan; Eda Gürlen; Pınar Köseoğlu (Anı Publishing, 2019)
The purpose of this research; biology teacher candidates are able to associate their scientific knowledge with their daily lives during their education. In context of this purpose, it is designed in form of case study.The study group of the study; on the basis of volunteerism, in Hacettepe University Biology Education Department, in the spring semester of 2017-2018, 26 teachers from 4th and 5th grade. Criteria sampling was used in the research purpose sampling methods. Biology was obtained by using semi-structured interview form in relation to the level of teacher candidates' ability to relate scientific information to their daily lives. In the analysis of the data obtained from interview questions, content analysis method was used. According to the findings obtained as a result of the research; biology teacher candidates can associate scientific knowledge with their daily lives to a great extent.